A study of the antimicrobial activity of the essential oil of Eucalyptus globulus Labillardiere (Myrtaceae) - Jabanes, Susan S.
The essential oil obtained by steam distillation from the fresh leaves and young stems of Eucalyptus globulus Labillardiere (Myrtaceae) was fractionated by column chromatography using pure chloroform as solvent. Three fractions were obtained. The crude oil and its fractions were subsequently tested for their antimicrobial activity using the following test organisms: Bacillus subtilis, Escherichia coli, Microbacterium avium, Staphylococcus aureus, Candida albicans, Microsporum canis, Aspergillus spp., Penicillium spp. The first fraction was found to be an antibacterial, inhibiting the growth of Bacillus subtilis, Escherichia coli, Microbacterium avium, Staphylococcus aureus, and an antifungal, inhibiting the growth of Candida albicans, Aspergillys spp., Penicillium spp. but inactive against Microsporum canis. The second fraction was found to be an antifungal, inhibiting the growth of Candida albicans, Aspergillys spp. and Penicillium spp. No antimicrobial activity was exhibited by the third fraction.